2013
DOI: 10.1021/nn400690e
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Formation of N-Doped Nanoarchitectures by Diffusion-Controlled on-Surface (Cyclo)Dehydrogenation of Heteroaromatics

Abstract: Surface-assisted cyclodehydrogenation and dehydrogenative polymerization of polycyclic (hetero)aromatic hydrocarbons (PAH) are among the most important strategies for bottom-up assembly of new nanostructures from their molecular building blocks. Although diverse compounds have been formed in recent years using this methodology, a limited knowledge on the molecular machinery operating at the nanoscale has prevented a rational control of the reaction outcome. We show that the strength of the PAH-substrate intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 55 publications
4
62
0
Order By: Relevance
“…In particular, in ref. [1] we demonstrated that the structures formed on different coinage metal surfaces from the same PAH (namely DiPy [5]DBH) are analogous, but their relative formation temperatures strongly depend on the substrate. Most of the works published until now in this field use Scanning Tunnelling Microscopy (STM) or non-contact Atomic Force Microscopy (nc-AFM) 8 images to identify both, precursors and reaction products, while spectroscopic characterization of the processes is less common.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…In particular, in ref. [1] we demonstrated that the structures formed on different coinage metal surfaces from the same PAH (namely DiPy [5]DBH) are analogous, but their relative formation temperatures strongly depend on the substrate. Most of the works published until now in this field use Scanning Tunnelling Microscopy (STM) or non-contact Atomic Force Microscopy (nc-AFM) 8 images to identify both, precursors and reaction products, while spectroscopic characterization of the processes is less common.…”
Section: Introductionmentioning
confidence: 82%
“…1 The experiments have been carried out in three ultra-high vacuum (UHV) chambers, all with a base pressure of 1×10 -10 mbar. In all of them, the molecular powder was sublimated from a homemade Ta crucible annealed at 575 K controlled by a type-K thermocouple spot-welded to it.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations